Flatness Improvement Technology of Febry-Perrot Interferometer via Simultaneous Modulation of 3-Channel PZT Actuators and Interface Electronics Implementation 다채널 PZT 엑추에이터의 동시 조작에 기반한 FPI 미러의 평탄도 향상 기술 및 인터페이스 회로의 개발 - Park, Jung Woong; Jeong, Sang Won; Lee, Hyun Ho; Jang, Min Jun; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2024)
This study presents the development of a lead zirconate titanate (PZT)-based Febry-Perrot Interferometer (FPI) tailored for the selective transmission of specific wavelengths. Our FPI integrates two mirrors, 3-channel PZT actuators, and interfacing electronics, enabling dynamic adjustments in PZT actuator lengths through voltage application. The interface electronics facilitate precise voltage control over the multi-channel PZT actuators, regulating the air gap between mirrors. Experimental results demonstrate the effectiveness of the developed interfacing electronics in modulating the transmission peak of light, resulting in a narrowed full width at half maximum (FWHM) and a heightened transmittance rate at targeted wavelengths. Additionally, the interface adeptly manages multi-channel PZT voltages, mitigating potential mirror alignment discrepancies during FPI assembly. By optimizing the air gap between the mirrors, significant enhancements in the center wavelength of the transmitted beam are achieved.
Keywords: Air-gaps; Electronic implementations; Fabry-perrot; Fabry-perrot interferometer; Interface electronics; Lead zirconate-titanate; Multi channel; PZT; PZT actuator; Refractive layer; Actuators; Air gap; Fabry-Perrot Interferometer; Interface electronics; PZT; Refractive layer